Spatial analysis of a coastal area for conservation and fishery of mangrove edible crab (Ucides cordatus) - Santos, Luciana C. M. [UNESP]; Rollo, Mario M. [UNESP]; Costa, Tânia M. [UNESP]; Pinheiro, Marcelo A. A. [UNESP]; Dahdouh-Guebas, Farid; Bitencourt, Marisa D. (Coastal Education and Research Foundation, 2016)
Mangroves are productive ecosystems of tropical coastal landscapes, constituting habitat for many commercial fisheries, as the crab Ucides cordatus. In Brazil this crab holds a major socio-economic importance for artisanal fishery, but with obvious decline on their productivity. In this study we determined and mapped the more suitable mangrove areas for the conservation and fishery of this crab in the São Francisco River Estuary (Northeastern Brazil). We applied a Multi-Criteria Evaluation (MCE) in a GIS environment. Ten criteria in total were used, including crab biotic parameters, land use/cover and social factors. Maps of each criterion were produced by GIS techniques with CBERS and SPOT images and by field data. Mangroves more suitable for the conservation of U. cordatus (9.4 km2) are near to the river mouth, due to high density and frequency of non-commercial size crabs (NCSC), low density of commercial size crabs (CSC), small crabs and low degree of use for fishery. On the other hand, the mangroves for the crab fishery occurred with a similar area (10.2 km2) located farther away from the river mouth, with a high density and frequency of CSC, low density of NCSC, big crabs, medium-high degree of use for fishery and near to the villages. These information and thematic maps can aid government agencies in delineating extractive and fishery exclusion areas, thus contributing to the management plan for this species.
Keywords: Fishery management; Mangrove; Remote sensing